2015
DOI: 10.1103/physrevb.92.045309
|View full text |Cite
|
Sign up to set email alerts
|

Phonon thermoelectric transistors and rectifiers

Abstract: We describe nonlinear phonon-thermoelectric devices where charge current and electronic and phononic heat currents are coupled, driven by voltage and temperature biases, when phonon-assisted inelastic processes dominate the transport. Our thermoelectric transistors and rectifiers can be realized in a gate-tunable double quantum-dot system embedded in a nanowire which is realizable within current technology. The inelastic electron-phonon scattering processes are found to induce pronounced charge, heat, and cros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
145
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 53 publications
1
145
1
Order By: Relevance
“…Particularly, when ǫ d = ǫ a , calculations of transport in double quantum dot systems show that the inelastic component of the current can dominate the elastic term 47 . We also justify our model in the language of molecular orbitals, electronic eigenstates of the molecule.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, when ǫ d = ǫ a , calculations of transport in double quantum dot systems show that the inelastic component of the current can dominate the elastic term 47 . We also justify our model in the language of molecular orbitals, electronic eigenstates of the molecule.…”
Section: Modelmentioning
confidence: 99%
“…This simplification allows us to reach closed analytic results for the CGF. The contributing of elastic tunneling processes can be included in an additive manner 47 , a reasonable approximation at weak coupling 41 . We diagonalize the electronic Hamiltonian, H el ≡ H M + H L + H R + H C , and write it down in terms of a new set of fermionic operators (a l/r , a † l/r ),…”
Section: Modelmentioning
confidence: 99%
“…On the other hand, various devices running on energy exchanges with a third bosonic reservoir have been discussed. In particular, phonon-driven mechanisms have been considered at a theoretical level in two-levels systems or chains of localized states along nanowires (NWs) in the context of phonon-assisted hopping transport [31,32,37]. More generally, NW-based devices have been at the heart of experimental studies on future thermoelectrics for over a decade [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays the idea of exploiting multiterminal thermoelectric setups is driving the field through a new season of very intense activity . In contrast with conventional two-terminal thermoelectrics, multiterminal thermoelectrics aims at studying a conductor connected, in addition to the two reservoirs at its ends, to (at least) one other reservoir, be it a mere probe [4][5][6][7][8]21], a normal electronic reservoir [9][10][11], a superconducting lead [11][12][13][14], or a reservoir of fermionic [15][16][17]21,22] or bosonic [23][24][25][26][27][28][29][30][31][32][33][34]36] nature that can only exchange energy with the system. Investigations carried out so far have shown that the multiterminal geometry has generally a positive impact on the performance of the thermoelectric devices [7,9,13,21,30], compared to their two-terminal counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the QME as described here can be used to examine a range of transport problems, by turning on/off different reservoirs. Besides the analysis of inelastic electronic conduction with anharmonic modes, one can use this method and study the operation of phononthermoelectric transistors 53 and phononic thermal junctions with harmonic and anharmonic local modes, to demonstrate nonlinear function such as thermal rectification and negative differential thermal conductance 62 . To derive Eq.…”
Section: Discussionmentioning
confidence: 99%